Advanced Maternal Age And Obstetric Morbidity - Ayala-Peralta, Félix (2016)
Objective: To evaluate the obstetric outcome of pregnant women with advanced maternal age (EMA) treated at the NationalMaternal Perinatal Institute. Materials and methods: Observational, descriptive and retrospective study of 321 maternaloutgoings occurred during the period from January 1 to June 30, 2016.